Interaction between siloxane-hydrogel contact lenses and eye cosmetics: Aluminum as a marker of adsorbed mascara deposits. Issue 5 (June 2021) - Zeri, Fabrizio; Borghesi, Alessandro; Acciarri, Maurizio; Tavazzi, Silvia
The purpose of the study was to investigate the presence of mascara deposits on polymeric siloxane-hydrogel contact lenses (CLs) after in vivo 8 h of wear and to compare the affinity to mascara of two siloxane-hydrogels through in vitro contamination tests. The siloxane-hydrogel CLs were the Filcon V monthly replacement OPEN30 and the Delefilcon A daily disposable DAILIES TOTAL1 showing a water gradient from the core to the outermost hydrophilic surface layer. The investigated cosmetic was a blue mascara. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) were carried out on new CLs, CLs exposed in vitro to mascara, and CLs worn for 8 h by mascara wearers (after rinsing the CLs in sodium chloride solution). Images by an optical microscope were acquired and processed on new CLs and CLs treated in vitro. EDX analyses on mascara allowed to characterize its elemental composition including aluminum (Al), which is neither a tear nor a CL component, thus being a marker of the presence of mascara deposits on polymeric siloxane-hydrogels. Adsorbed deposits containing Al were observed by SEM/EDX on all worn CLs of both materials, which showed a special affinity for the mascara components, more marked than for the tear components. By processing the images taken by optical microscopy after in vitro tests, the presence of mascara deposits was found to be more than two times higher in Delefilcon A compared to Filcon V CLs.